2017
DOI: 10.1142/s2424922x17500073
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Evolution in Predictive Models and Impacting Factors in Customer Churn

Abstract: The information-based prediction models using machine learning techniques have gained massive popularity during the last few decades. Such models have been applied in a number of domains such as medical diagnosis, crime prediction, movies rating, etc. Similar is the trend in telecom industry where prediction models have been applied to predict the dissatisfied customers who are likely to change the service provider. Due to immense financial cost of customer churn in telecom, the companies from all over the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…e same finding as mentioned before has also been published and confirmed in some other relevant papers that had also used the same deep learning methods to predict customer's churn in the business of the telecommunication field, and it can be seen in [33,34]. us, we can gladly inscribe that the approaches which are used to configure the hyperparameters in a neural network where NNs are used for modelling the churn rate seem to be still lacking on a larger scale in the telecommunication sector, and this work has widely been explored in this article, respectively.…”
Section: Techniques For Churn Predictionsupporting
confidence: 80%
“…e same finding as mentioned before has also been published and confirmed in some other relevant papers that had also used the same deep learning methods to predict customer's churn in the business of the telecommunication field, and it can be seen in [33,34]. us, we can gladly inscribe that the approaches which are used to configure the hyperparameters in a neural network where NNs are used for modelling the churn rate seem to be still lacking on a larger scale in the telecommunication sector, and this work has widely been explored in this article, respectively.…”
Section: Techniques For Churn Predictionsupporting
confidence: 80%
“…Huang and Wang [9] improved the Iterative Dichotomiser 3 (ID3) algorithm with weighted entropy, constructed a decision tree model based on the improved algorithm, and proved the effectiveness and accuracy of the improved algorithm through empirical analysis. Ahmed et al [10] relied on the genetic algorithm (GA) to identify eight indices of customer churn from basic and transaction data, combined the SVM and neural network (NN) into a hybrid prediction model, and confirmed that the hybrid model is more accurate and efficient than the SVM and NN along.…”
Section: Literature Reviewmentioning
confidence: 99%
“…using several learners such as decision trees, support vector machines, neural networks, probabilistic models such as Bayes, etc. [6] E-commerce has provided new opportunities for both businesses and consumers to easily share information, find and buy a product, increasing the ease of movement from one company to another as well as to increase the risk of churn. Studies develop churn prediction model [7] by testing the forecasting capability of the support vector machine (SVM).…”
Section: Current Researchmentioning
confidence: 99%